Validation study on left ventricular ejection time determination in impedance cardiography using arterial pulse wave - Julia Loschel, 1989- author; Eko Supriyanto; Fakulti Biosains dan Kejuruteraan Perubatan (2015)
Thesis (Sarjana Kejuruteraan Bioperubatan) - Universiti Teknologi Malaysia, 2015